The Implementation of Intercultural Communicative Competence-based Learning in Senior High School Context - admin, admin; Husain, uriah Fadliah; Atmowardoyo, Haryanto; Noni, Nurdin (Celebes Journal of Language Studies, 2023)
This research studies about the implementation of Intercultural Communicative Competence (ICC)-based learning in senior high school context. This research aims to investigate the way the teacher implements ICC-based learning in senior high school context, to know the students’ perception towards the implementation of ICC-based learning and to reveal the challenges faced by the teacher in implementing ICC-based learning in the classroom. Using qualitative method, the researcher found the two main research findings. The first, researcher found that ICC-based learning in the classroom was implemented through teaching activities that involved all elements of ICC. The last, the result shows that there are two big challenges in the implementation of ICC-based learning. Those are the teacher's cleverness and commitment to find a cultural material for ELT classroom and the students' readiness and motivation to accept the intercultural lesson.